Prevalence and Predisposing Factors of Pediculosis Capitis on Elementary School Students at Jatinangor - Karimah, Arani; Hidayah, Risa Miliawati Nurul; Dahlan, Anisah (Althea Medical Journal, 2016)
Background: Pediculosis capitis is a lice infestation on scalp with high prevalence on the age of elementaryÂ school students. It is one of neglected diseases. Predisposing factors such as hair type and length, selfÂ higienities, and sosioeconomic can influence prevalence of pediculosis capitis. The aim of the study wasÂ to reveal pediculosis capitis prevalence and its predisposing factors on elementary school students atÂ Jatinangor.Methods: This study used cross-sectional descriptive method which conducted in September 2014 atÂ Jatinangor. The study subjects were elementary school students graded 1 to 6 taken from two elementaryÂ schools by multistage random sampling technique. Data was presented in a table.Results: The prevalence of pediculosis capitis from 123 study subjects was 55.3%. The prevalence foundÂ on girls (81.3%), students with long hair (76.9%), students with curly hair (52.9%), students of third gradeÂ (66.7%), students with washing hair three times or more in a week (59.3%), students with mothers onlyÂ graduated from elementary school (60%), students parents with income less than one million rupiahÂ (63.3%), students staying with four or more persons in the same house (56.3%), and students with havingÂ previous this disease (60.2%).Conclusions: Pediculosis capitis prevalence on elementary school students is quite high. The prevalenceÂ based on subject characteristics and sosioeconomic is suitable with previous studies. [AMJ.2016;3(2):254â8]DOI:Â 10.15850/amj.v3n2.787